1999
DOI: 10.3402/tellusa.v51i5.14506
|View full text |Cite
|
Sign up to set email alerts
|

Stability properties of a barotropic surface-water jet observed in the Denmark Strait

Abstract: Observational data from a transect of the Denmark Strait have shown a rapid (1 m/s) southward-flowing barotropic surface jet. A linear stability analysis of the jet suggests that it may be unstable with respect to wavelike perturbations. The most unstable wave proved to be sinuous, i.e., meandering, with a growth rate of around 19 h (in terms of an e-folding time), a phase velocity of approximately 25 cm/s and wavelengths of around 40 km. Associated hydrographic data indicate that the local mixing of the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Since 1993 the Nordic World Ocean Circulation Experiment (WOCE) and European Community-Variability of Exchanges in Northern Seas (EC-VEINS) programs have undertaken a number of cruises to the Denmark Strait sill and nearby regions. Two of these cruises on the Finnish R/V Aranda are described by Fristedt et al (1999) and Rudels et al (1999). In recent years the Institut für Meereskunde (IFM), Kiel, has also undertaken a number of cruises with the R/V Poseidon and other German vessels to the region, some of which have been briefly described by Krauss and Käse (1998).…”
Section: Past Observations Of the Dsomentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1993 the Nordic World Ocean Circulation Experiment (WOCE) and European Community-Variability of Exchanges in Northern Seas (EC-VEINS) programs have undertaken a number of cruises to the Denmark Strait sill and nearby regions. Two of these cruises on the Finnish R/V Aranda are described by Fristedt et al (1999) and Rudels et al (1999). In recent years the Institut für Meereskunde (IFM), Kiel, has also undertaken a number of cruises with the R/V Poseidon and other German vessels to the region, some of which have been briefly described by Krauss and Käse (1998).…”
Section: Past Observations Of the Dsomentioning
confidence: 99%
“…In this case, the inhomogeneities produced near or before the sill could become amplified during the descent of the slope. In this case, the models of Smith (1976) or Fristedt et al (1999) would be more applicable.…”
Section: ) Other Mechanisms For Cross-isobathmentioning
confidence: 99%
“…It was demonstrated that the dominant period of variability in current meter records matched that of the most unstable baroclinic wave in a linear, idealized flow in Denmark Strait. An alternate theory was later proposed after the discovery of a weakly stratified southward-flowing current in Denmark Strait [Fristedt et al, 1999]. The current was shown to have unstable growth rates comparable to the baroclinic wave proposed by Smith [1976], that could be responsible for fluctuations in the overflow.…”
Section: Introductionmentioning
confidence: 99%
“…At this location the strongest current (up to 90 cm/s) was found over the Icelandic slope where the bottom depth was between 500–600 m supporting the continuation of the current observed at IS7 towards the sill. The structure of the overflow at the sill has been investigated using a vessel mounted ADCP (Acoustic Doppler Current Profiler) and it was observed that the current behaved like a barotropic jet [ Fristedt et al , 1999]. This was also the case at IS7 where currents were measured at 80, 500 and 750 m depth and they all showed a current of ca.…”
Section: Introductionmentioning
confidence: 99%